Studies on functional education and literacy a handbook and user's guide - University of the Philippines (Diliman). Center for Integrative and Development Studies. Education Research Program; Philippines. Bureau of Non-Formal Education (Quezon City UP-ERP Research Team, 1996)
This book is an attempt to bridge the gap between research and practice and to ensure that researchers, policy-makers and practitioners in literacy and functional education can find a common ground for continued communication and cooperation towards the shared objective of helping our people to achieve the kind of education that is functional to their lives, and relevant to their needs and aspirations.
"This Handbook and User's Guide is an attempt to ensure that researchers, policy-makers and practitioners in literacy and functional education can find a common ground for continued communication and cooperation towards the shared objective of helping our people to achieve the kind of education that is functional to their lives, and relevant to their needs and aspirations."
"This study was undertaken to produce an abstract bibliography of thesis and dissertations that will minimize or solve the problem of bibliographic control of unpublished thesis and dissertations in fisheries-related subjects. This study is in two parts, Part I consists of the introduction, review or related literature, methodology, presentation, analysis, and interpretations of data, and the summary, conclusions and recommendations, including list or references and the appendices, Part II is the abstract bibliography consisting of 344 entries arranged by computerized Master File Number (MFN) and accompanied by author, title, taxonomic and geographic indexes."
Keywords: Literacy -- Government policy -- Philippines -- Handbooks, manuals, etc; Literacy programs -- Philippines -- Handbooks, manuals, etc; Functional literacy -- Philippines -- Handbooks, manuals, etc; Education -- Philippines -- Handbooks, manuals, etc; Non-formal education -- Government policy -- Philippines -- Handbooks, manuals, etc